Low Background Signal Readout Electronics for the Majorana Demonstrator. (April 2015) - Guinn, I; Abgrall, N; Avignone, F T; Barabash, A S; Bertrand, F E; Brudanin, V; Busch, M; Buuck, M; Byram, D; Caldwell, A S; Chan, Y-D; Christofferson, C D; et al.
Abstract: The Majorana Demonstrator is a planned 40 kg array of Germanium detectors intended to demonstrate the feasibility of constructing a tonne-scale experiment that will seek neutrinoless double beta decay (0 νββ ) in 76 Ge. Such an experiment would require backgrounds of less than 1 count/tonne-year in the 4 keV region of interest around the 2039 keV Q-value of the ββ decay. Designing low-noise electronics, which must be placed in close proximity to the detectors, presents a challenge to reaching this background target. This paper will discuss the Majorana collaboration's solutions to some of these challenges.